2021
DOI: 10.1111/iwj.13656
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of diabetic foot care and the prevalence of diabetic foot ulcers among diabetic patients of selected hospitals in the Volta Region, Ghana

Abstract: Diabetic foot ulcers (DFUs) are a common but serious complication of diabetes mellitus (DM). The factors distressing the worth of diabetic foot care (DFC) are knowledge and practice. Foot ulcers are the main cause of amputation and death in people suffering from DM. This study assessed the knowledge and practice of DFC and the prevalence of DFUs and its associated factors among diabetic patients of selected hospitals in the Volta Region, Ghana. A multihospitalbased cross-sectional study was conducted among 473… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 52 publications
5
44
0
1
Order By: Relevance
“…The results of the current study were confirmed the high level of interleukin-6 (IL-6) in the serum of patients with diabetic foot, and this occurs as a result of the increase in the inflammatory process that leads to the response of the immune system and the activation of immune cells. This study agreed with Lanys et al, 2021 [14] , who explained in his study that diabetic foot disease is associated with high levels of interleukin-6 in the blood of people with this disease.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study were confirmed the high level of interleukin-6 (IL-6) in the serum of patients with diabetic foot, and this occurs as a result of the increase in the inflammatory process that leads to the response of the immune system and the activation of immune cells. This study agreed with Lanys et al, 2021 [14] , who explained in his study that diabetic foot disease is associated with high levels of interleukin-6 in the blood of people with this disease.…”
Section: Discussionsupporting
confidence: 93%
“…Another reason for "not sure" is because the interview was administered sometimes in the presence of relatives, whereby most postpartum mothers felt timid to voice their discontent about some of the disliked services that had been rendered to them. A cumulative percentage method was employed, which considers only the positive answer (31). The total cumulative percentage is calculated and rounded up to 100%.…”
Section: Assessment Of Postnatal Mothers' Satisfaction With Skilled Deliverymentioning
confidence: 99%
“…This was a multihospital-based cross-sectional study conducted in the Volta Region, Ghana, between September 2019 and December 2019. Details of the study methodology, first 23 and second papers 24 , have been published. The final paper is different and unique in terms of content.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic patients who visited the designated hospitals during their appointments were recruited through a systematic sampling technique 23 . Patients who were medically stable and willing to participate in the study were interviewed face-to-face 23 . Sick patients who were unable to talk, those who disagreed to participate and gestational diabetic patients were excluded from the study 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation